2020
DOI: 10.1115/1.4046375
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer Analysis of Phan-Thien-Tanner Immiscible Fluids Under Electro-Osmotic and Pressure-Driven Effects in a Slit Microchannel

Abstract: Because the pumping of samples by viscous drag forces and the use of flow-focusing for several sheath flows are widely used in microfluidic devices applications, the present investigation treats about the transport of multilayer immiscible viscoelastic fluids into a slit microchannel by electro-osmotic and pressure-driven effects. The mathematical formulation for the steady-state analysis of the flow field is based on the Poisson–Boltzmann equation and the Cauchy momentum equation. Each fluid layer has indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…which has been solved using the inverse matrix method in a process analogous to that of the electric potential distribution. Therefore, the constants D n and E n in Equation (49), and the constants A n and B n found through Equation ( 51), are replaced into Equation (50), where the inverse Laplace transform is numerically applied to solve the velocity distribution in this electroosmotic flow. To this, the method based on concentrated matrix exponential (CME) distributions is used [66]; in this framework, a finite linear combination of the transform values approximatesū, viā…”
Section: Velocity Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…which has been solved using the inverse matrix method in a process analogous to that of the electric potential distribution. Therefore, the constants D n and E n in Equation (49), and the constants A n and B n found through Equation ( 51), are replaced into Equation (50), where the inverse Laplace transform is numerically applied to solve the velocity distribution in this electroosmotic flow. To this, the method based on concentrated matrix exponential (CME) distributions is used [66]; in this framework, a finite linear combination of the transform values approximatesū, viā…”
Section: Velocity Distributionmentioning
confidence: 99%
“…However, other studies about the flow of two immiscible parallel fluids, consider that both fluids are conductive (i.e., fluids based in electrolytic solutions), increasing the complexity of the electrostatic boundary conditions in the liquid-liquid interface through a potential difference and the Gauss’s law for the electrical displacement, together with the hydrodynamic boundary conditions via the combination of viscous and electric Maxwell stresses [ 44 , 45 , 46 , 47 ]. In addition, to cover the different flow-focusing applications in microdevices, the study of parallel flows under electrokinetic effects also has been extended to multi-layer systems [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Torres et al 16 studied the electro‐osmotic flow of multilayer fluid in a narrow capillary and revealed that produced velocity gradient leads to strong changes in the velocity. Escandón et al 17 investigated the flow of multilayered viscoelastic fluid in a slit microchannel in the presence of pressure‐driven and electroosmotic effects and observed that characteristics of multilayer flow are associated with the type of electrolyte solutions. Escandón et al 18 discussed the transient electroosmotic flow of multilayer Maxwell fluids in a slit microchannel.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the micropump that uses pressure-driven forces requires mobile parts and can drive fluids over a broad range of velocities and pressures. Another control method for multiphase flows is the electroosmotic flow [61][62][63][64][65][66][67][68][69][70][71][72][73]. The driving force is caused by the interaction between the net charged density in the electric double layer and an applied electric field in the flow domain.…”
Section: Introductionmentioning
confidence: 99%